A geochemical profile through the Uitkomst Complex on the farm Slaaihoek, with special reference to the platinum-group elements and Sm-Nd isotopes - Maier, Wolfgang D. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2006.